2009
DOI: 10.1007/s10800-008-9758-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hot-pressing temperature on the performance of PEMFC and catalytic activity

Abstract: The influence of hot-pressing temperature on catalytic activity and the performance of proton exchange membrane fuel cells (PEMFCs) was investigated using current-voltage (I-V) polarization, electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). EIS provided detailed information on the contribution, from high to low frequencies, of internal impedance (R s ), interfacial impedance (R if ) and reaction impedance (R rxn ). The ohmic resistance of the cell (R X ) was estimated from the I-V diagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A wide range of process conditions are reported in the literature with hot press compression pressure ranging from 1380 kPa to 49,000 kPa, temperature from 90 o C to 170 o C, and time of compression from 90 s to 360 s [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][35][36][37][38][39][40][41]. Depending on the materials used, a large number of internal parameters affect the hot-pressing process, which explains why such a wide range of conditions are reported.…”
Section: Membrane Electrode Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of process conditions are reported in the literature with hot press compression pressure ranging from 1380 kPa to 49,000 kPa, temperature from 90 o C to 170 o C, and time of compression from 90 s to 360 s [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][35][36][37][38][39][40][41]. Depending on the materials used, a large number of internal parameters affect the hot-pressing process, which explains why such a wide range of conditions are reported.…”
Section: Membrane Electrode Assemblymentioning
confidence: 99%
“…SEM) and electrochemical analysis (electrochemical surface area and impedance spectroscopy) [52]. These studies have shown that the pressing temperature has the most important influence on the bonding process between electrode and electrolyte [2,36,52].…”
Section: Internal Parameters Affecting Hot-pressingmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main parameters in the hot-pressing process are temperature (T ), pressure (P), and duration (T ). Typically, the hot-pressing temperature is selected between the glass transition temperature (T g ¼ 115 C) of the Nafion and the decomposition temperature (T d > 280 C) of the Nafion 1100 series of proton-exchange membranes [22,24]. Only at the temperature above T g , the Nafion membrane is softened and can be attached to the electrodes under a high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…CCMs are the predominant construction in research studies and are typically found to have better performance. 1,2 Direct coating of CCMs is challenging due to membrane swelling in the catalyst ink solvents. 3 Lab-scale direct-coated CCMs are often fabricated by ultrasonic spray coating where the membrane can be mechanically stabilized on a vacuum plate to prevent shrinking and swelling during the coating process.…”
mentioning
confidence: 99%